Approaches to interculturality. A reflection from the anthropological perspective - SALDAÑA DUQUE , Reina (Utopía y Praxis Latinoamericana, 2022)
This article is the result of reflections on interculturality from an anthropological perspective proposed by the intercultural philosophy of the teacher Raúl Fornet-Betancourt, in which case it is deployed in the doctoral thesis “Pedagogy and interculturality in Latin America. A reading from the educational processes in four social movements ", where it seeks to propose a contextual framework to account for pedagogies in Latin America from an intercultural perspective, in a humanist key. Starting from intercultural hermeneutics, it was sought to understand the emergence of pedagogies, of other forms of education that affect the configuration of situated and contextualized pedagogies. Understandings are made that recognize the subject, the context, the cultures and the epistemes through their history, their struggle for social and political demand, which throughout the ages has prevailed.